High gain triple-band metamaterial-based antipodal vivaldi mimo antenna for 5g communications - Saeidi, T. (MDPI AG, 2021)
This paper presents a miniaturized dual-polarized Multiple Input Multiple Output (MIMO) antenna with high isolation. The antenna meets the constraints of sub-6 GHz 5G and the smartphonesâ X-band communications. A vertically polarized modified antipodal Vivaldi antenna and a horizontally polarized spiral antenna are designed and integrated, and then their performance is investigated. Three frequency bands of 3.8 GHz, 5.2 GHz, and 8.0 GHz are considered, and the proposed dual-polarized antenna is studied. High isolation of greater than 20 dB is obtained after integration of metamaterial elements, and without applying any other decoupling methods. The proposed triple-band metamaterial-based antenna has 1.6 GHz bandwidth (BW) (2.9 GHzâ4.5 GHz), 13.5 dBi gain, and 98 radiation efficiency at 3.8 GHz. At 5.2 GHz it provides 1.2 GHz BW, 9.5 dBi gain, and 96 radiation efficiency. At 8.0 GHz it has 1 GHz BW, 6.75 dBi gain, and 92 radiation efficiency. Four antenna elements (with eight ports) were laid out orthogonally at the four corners of a mobile printed circuit board (PCB) to be utilized as a MIMO antenna for 5G communications. The performance of the MIMO antenna is examined and reported. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.